Unifying high- and low-resolution observations to constrain the dayside atmosphere of KELT-20b/MASCARA-2b - Kasper, David; Bean, Jacob L.; Line, Michael R.; Seifahrt, Andreas; Brady, Madison T.; Lothringer, Joshua D.; Pino, Lorenzo; Fu, Guangwei; Pelletier, Stefan; Stürmer, Julian; Benneke, Björn; Brogi, Matteo; et al. (The astronomical journal, 2022)
We present high-resolution dayside thermal emission observations of the exoplanet KELT-20b/MASCARA-2b using the MAROON-X spectrograph. Applying the cross-correlation method with both empirical and theoretical masks and a retrieval analysis, we confirm previous detections of Fe i emission lines and we detect Ni i for the first time in the planet (at 4.7σ confidence). We do not see evidence for additional species in the MAROON-X data, including notably predicted thermal inversion agents TiO and VO, their atomic constituents Ti i and V i, and previously claimed species Fe ii and Cr i. We also perform a joint retrieval with existing Hubble Space Telescope/WFC3 spectroscopy and Spitzer/IRAC photometry. This allows us to place bounded constraints on the abundances of Fe i, H2O, and CO, and to place a stringent upper limit on the TiO abundance. The results are consistent with KELT-20b having a solar to slightly supersolar composition atmosphere in terms of the bulk metal enrichment, and the carbon-to-oxygen and iron-to-oxygen ratios. However, the TiO volume mixing ratio upper limit (10−7.6 at 99% confidence) is inconsistent with this picture, which, along with the nondetection of Ti i, points to sequestration of Ti species, possibly due to nightside condensation. The lack of TiO but the presence of a large H2O emission feature in the WFC3 data is challenging to reconcile within the context of 1D self-consistent, radiative-convective models.